Uma Abordagem sobre a logística reversa dos resíduos sólidos em uma empresa de engenharia do Estado do Ceará - Pimentel, Ana Carolina Lima (2014)
The present dissertation is focused on reverse logistics of construction solid waste. Throughout this work demonstrate the economic hardship and other barriers that companies of this segment, especially infrastructure, face to meet the current environmental legislation and proposes alternatives to the situations encountered by logistics to direct your resources and efforts. What makes this relevant research is increasing the strategic value of solid waste management. More than providing the product within the expectation of the client need to act until the end of the useful life of the goods or services. Fruit of an environmental conscience that gen erated even more challenges and costs for the production process, but that no more ignore the issue of risk the image to the supervision of public authorities. The generation of solid waste is directly proportional to the industrial development and populat ion increase, what's making this increasingly complex issue. The methodology applied to this research can be classified as qualitative, descriptive and applied through a case study developed in an engineering company from Ceará facing metroferroviárias act ivities and wind park, demonstrating the involvement of reverse chain of solid waste of the works and their performance. Through the applied questionnaires, unstructured interviews and documentary research, it has been seen that the organization is in the process of implementing an environmental management system. The study concluded that the human factor has a direct impact on the material flow planning. Were pointed to the situations found to direct better the resources and efforts to generate an improvem ent and greater reliability in the disposal of the waste in relation to current situation